2020
DOI: 10.5194/gc-3-279-2020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an educational program on earthquake awareness and preparedness in Nepal

Abstract: Abstract. Scientific education of local communities is key in helping to reduce the risk associated with natural disasters such as earthquakes. Western Nepal has a history of major seismic events and is highly prone to further earthquakes; however, the majority of the population is not aware about or prepared for them. To increase earthquake awareness and improve preparedness, a seismology education program was established at 22 schools in Nepal. At each school, educational activities were performed by teachin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…Here, NST recognised native species as such better than non-NST, and did not select correctly non-native species or IAS. These results were similar to other studies on perception of IAS 10 , 16 , 25 , 26 , and to others on people’s awareness of natural disasters 27 . Similarly, Remmele and Lindemann-Matthies 10 found that biology teacher students identified IAS better than teacher students of other subjects, and more often selected management strategies to control them.…”
Section: Discussionsupporting
confidence: 92%
“…Here, NST recognised native species as such better than non-NST, and did not select correctly non-native species or IAS. These results were similar to other studies on perception of IAS 10 , 16 , 25 , 26 , and to others on people’s awareness of natural disasters 27 . Similarly, Remmele and Lindemann-Matthies 10 found that biology teacher students identified IAS better than teacher students of other subjects, and more often selected management strategies to control them.…”
Section: Discussionsupporting
confidence: 92%
“…In the above research interesting information on earthquakes, their religious and historical contexts as well as physical causes have been gathered from Hindu literature, which are of direct use for teaching earthquake related topics at school. Our Seismology at school in Nepal program (Subedi et al, 2020a) is currently running in 30 schools in Central Nepal, and the program has already received very positive feedback showing that educational activities implemented at schools are effective in raising the awareness levels of children, promoting broader social learning in the community, and improving the adaptive capacities and preparedness for future earthquakes (Subedi et al, 2020b). One of the next objectives of the program is to reach more remote parts of the country, where earthquake education is not available at all, and where it is likely that traditional or religious beliefs are more widespread than in semi-urban areas or larger villages.…”
Section: Implications For Education and Communicationmentioning
confidence: 99%
“…In frame of our educational program that currently involves 30 schools and reaches thousands of students, the dichotomy between scientific and religious visions of earthquakes is a challenge. In an initial survey among students, less than two-thirds indicated the scientific reason for earthquakes (Subedi et al, 2020b). Two surveys were conducted in the Central Nepal and we have carefully analyzed the results assuming the fact that earthquake knowledge depends on several factors, for example, social status, family background, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In some societies, the lack of access to science-based earthquake information can hinder preparedness by cultivating misconceptions, such as those relating to fatalism and God's will (Yari et al, 2019;Paradise, 2005) or by blaming and shaming specific population groups (Simpson, 2011;Halvorson and Hamilton, 2007). Previous work has identified schoolbased disaster risk reduction (DRR) education as one of the main contributors to the long-term resilience and empowerment of communities (Subedi et al, 2020;Oktari et al, 2018;UNICEF, 2014;Twigg, 2009). An effective DRR curriculum can prepare children and youth to be agents of change by actively engaging them in learning about geohazard science and school safety measures and preparing them to share their learning with the wider community (see Mitchell et al, 2009, and references therein).…”
Section: Introductionmentioning
confidence: 99%